THE LEVEL OF CONSUMER SATISFACTION WITH THE NON-PRESCRIPTION DRUG INFORMATION SERVICE AT THE PHARMACY WEDOMARTANI YOGYAKARTA AREA - Nova Aprilia; Yosef Wijoyo (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
An essential pharmacy service is the pharmacists' information service on medications. This service will have an effect on improving customer satisfaction and raising awareness of the use of medications. Many clients are still unhappy with this service. This study aims to assess consumer satisfaction levels with the non-prescription drug information service provided at pharmacies in the Wedomartani area and identify gaps between consumer expectations and the actual service. This investigation is a cross-sectional, analytical, and observational study. A total of 142 customers, who bought over-the-counter medications at four pharmacies in the Wedomartani region between March and April 2022, served as respondents. The research instrument used is a service quality questionnaire with the servqual method. The questionnaires used have undergone validity tests, language comprehension tests, and reliability tests. There are two ways to complete surveys: offline (on paper) and online (using a Google form). Three methods are used to assess the data: gap analysis, customer satisfaction index computation, and importance-performance analysis (IPA). The findings revealed that (1) the results of the gap analysis were < 0 (negative value f), (2) the CSI analysis yielded a minimum value of 80%, and (3) there is a need to strengthen medication information services. The conclusions of this study are: there is still a gap between reality and expectations felt by consumers; Theoretically, drug information should be based on scientific information, but the delivery of drug information needs to be simplified so that it is easily understood by the recipient of the information...